Clinical effects of overwintered-stressed Chondrus Crispus and non-overwintered-stressed Chondrus crispus dietary supplementations - Palmieri, Beniamino; Vadalà, Maria; Laurino, Carmen (Asian Journal of Medical Sciences, 2018)
Background: Chondrus crispus is red seaweed widespread in the northern Atlantic coasts due to the high proteins, burden it is quite helpful supplement for some symptoms such as fatigue, asthenia, and weakness and for supporting skeletal muscles in sports athletes. Aims and Objectives: This retrospective observational “not inferiority” study investigates and compares the clinical effects of overwintered-stressed Chondrus Crispus and non-overwintered-stressed Chondrus crispus dietary supplementations for the treatment of musculoskeletal and articular symptomatology related diseases. Materials and Methods: Eighty patients were retrospectively reviewed through the Second Opinion Medical Network. Patients were prescribed 3 capsules/day after the main meals for 3 weeks of overwintered-stressed Chondrus Crispus or non-overwintered stressed Chondrus crispus dietary supplementations. Quality of life (QOL) assessment was evaluated by the Short Form-36 (SF-36) health survey questionnaire before starting the treatment and after the third week. Benefits declared by patients were also reported after the treatment in addition to some subjective observations related to the symptomatology and to the health status. Results: Fifty patients were treated with overwintered-stressed Chondrus Crispus and 30 patients were treated with the non-overwintered-stressed Chondrus crispus dietary supplementation. The general benefit of treatment with overwintered-stressed Chondrus Crispus was 76%, while that obtained with non-overwintered-stressed Chondrus crispus was 33.3% (P <0.01). Results of SF-36 general health status after the treatment demonstrated that 37 patients (74%) and 11 patients (36.7%) felt better than before in the overwintered-stressed Chondrus Crispus group and non-overwintered-stressed Chondrus crispus group, respectively (P < 0.01). A great improvement of subjective exhaustion, fatigue, pain, digestive, and peristalsis disturbances symptoms, in addition to mood and concentration amelioration that would be a consequence of symptomatology regression, was also observed. Conclusions: This retrospective observational comparative study evidences that overwintered-stressed Chondrus Crispus improved musculoskeletal and articular symptomatology related diseases better than non-overwintered-stressed Chondrus crispus. Asian Journal of Medical Sciences Vol.9(6) 2018 7-13